Catalyst‐Free Multicomponent Tandem Polymerizations of Aliphatic Amines, Activated Alkyne, and Formaldehyde toward Poly(tetrahydropyrimidine)s. Issue 5 (25th December 2022) - Wei, Bo; Chen, Longbin; Hu, Rongrong; Tang, Ben Zhong
Abstract: Poly(tetrahydropyrimidine)s are promising heterocyclic polymers with unique biocompatibility, antibacterial ability, inherent fluorescence property, and so on, whose development is limited by their synthetic approaches. Multicomponent polymerizations (MCPs) are a group of powerful tools for the facile construction of heterocyclic polymers from simple monomers. Herein, a catalyst‐free multicomponent tandem polymerization of aliphatic diamines, activated alkyne, and formaldehyde was developed at 60 °C in methanol in air to construct poly(tetrahydropyrimidine)s with well‐defined structures, high molecular weights ( M w up to 57700 g mol −1 ), high yields (up to 84%), and satisfactory thermal stability. The MCP was featured with commercially available monomers, high efficiency, catalyst‐free economic and mild condition, which was applicable to aliphatic diamines with complicated chemical reactivity, providing a robust and efficient approach for the synthesis of diversified heterocyclic polymers such as poly(tetrahydropyrimidine)s. Abstract : Poly(tetrahydropyrimidine)s are a group of promising heterocyclic polymers with unique biocompatibility, antibacterial ability, and inherent fluorescence property, and multicomponent polymerizations are powerful tools for the facile construction of heterocyclic polymers from simple monomers. Herein, a catalyst‐free multicomponent tandem polymerization of aliphatic diamines, activated alkynes and formaldehyde is developed at mild condition at 60 °C in methanol in air, affording poly(tetrahydropyrimidine)s with well‐defined structures, high molecular weights, high yields, and satisfactory thermal stability.